Investigative on the Molecular Mechanism of Licorice Flavonoids Anti-Melanoma by Network Pharmacology, 3D/2D-QSAR, Molecular Docking, and Molecular Dynamics Simulation - Hu, Yi; Wu, Yufan; Jiang, CuiPing; Wang, Zhuxian; Shen, Chunyan; Zhu, Zhaoming; Li, Hui; Zeng, Quanfu; Xue, Yaqi; Wang, Yuan; Liu, Li; Yi, Yankui; et al. (Frontiers in Chemistry, 2022)
Licorice flavonoids (LCF) are natural flavonoids isolated from glycyrrhiza, which are known to have anti-melanoma activities in vitro. However, the molecular mechanism of LCF anti-melanoma has not been fully understood. In this study, network pharmacology, 3D/2D-QSAR, molecular docking and molecular dynamics (MD) simulation were used to explore the molecular mechanism of LCF anti-melanoma. First of all, we screened the key active components and targets of LCF anti-melanoma by network pharmacology. Then the logIC50 values of the top 20 compounds were predicted by the 2D-QSAR pharmacophore model, and 7 highly active compounds were screened successfully. An optimal 3D-QSAR pharmacophore model for predicting the activity of LCF compounds was established by the HipHop method. The effectiveness of the 3D-QSAR pharmacophore was verified by a training set of compounds with known activity, and the possible decisive therapeutic effect of the potency group was inferred. Finally, molecular docking and MD simulation were used to verify the effective pharmacophore. In conclusion, this study established the structure-activity relationship of LCF and provided theoretical guidance for the research of LCF anti-melanoma.